2002
DOI: 10.1046/j.1432-1033.2002.03271.x
|View full text |Cite
|
Sign up to set email alerts
|

Solution structure of the Alzheimer amyloid β‐peptide (1–42) in an apolar microenvironment

Abstract: The major components of neuritic plaques found in Alzheimer disease (AD) are peptides known as amyloid β‐peptides (Aβ), which derive from the proteolitic cleavage of the amyloid precursor proteins. In vitro Aβ may undergo a conformational transition from a soluble form to aggregated, fibrillary β‐sheet structures, which seem to be neurotoxic. Alternatively, it has been suggested that an α‐helical form can be involved in a process of membrane poration, which would then trigger cellular death. Conformational stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

36
683
5
5

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 626 publications
(729 citation statements)
references
References 44 publications
36
683
5
5
Order By: Relevance
“…We use the mostly ␣-helical A␤ monomer conformation from the Protein Data Bank (36) as a starting conformation (37,38). We place 32 well separated peptides into our box and then perform a DMD simulation at a high temperature (T ϭ 2.0 E HB ͞k B ), recording the 32-peptide conformation every 10,000 simulation steps.…”
Section: Resultsmentioning
confidence: 99%
“…We use the mostly ␣-helical A␤ monomer conformation from the Protein Data Bank (36) as a starting conformation (37,38). We place 32 well separated peptides into our box and then perform a DMD simulation at a high temperature (T ϭ 2.0 E HB ͞k B ), recording the 32-peptide conformation every 10,000 simulation steps.…”
Section: Resultsmentioning
confidence: 99%
“…The initial coordinates of Aβ1−42 monomer were taken from model 1 of PDB entry 1IYT. 63 This conformation observed by NMR in an apolar environment is characterized by two α-helices spanning residues 8−25 and 28−39 ( Figure 1B). The monomer with the N-and C-termini treated as NH 3 + and COO − was then replicated and translated to obtain the initial dimer structures in a parallel orientation with no interchain atomic distances of <10 Å.…”
Section: ■ Methodsmentioning
confidence: 91%
“…On the other hand, NMR results show conformations varying from ␣-helical structure in a nonpolar solution 8 to disordered N-terminal and C-terminal tails with consistent turn regions as determined by electrospray mass spectroscopy and implicit solvent MD. 26,27 The side chain of most hydrophobic residues found in the shorter arm point outward, providing a hydrophobic platform for an association between A␤ monomer. This is consistent with the simulation by Tarus et al 28 of dimerization of A␤ 10-35 using umbrella sampling and MD.…”
Section: -3mentioning
confidence: 99%
“…Ma and Nussinov 11 suggested that at high temperature fragments A␤ [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] and A␤ form a strand-loop-strand structure with parallel ␤ sheet, with an interior salt bridge between Asp23 and Lys28 residues as a major element of the fibril structure. On the other hand, computational studies using coarse-grained as well as atomistic atom models suggest the formation of antiparallel ␤ sheets by A␤ [16][17][18][19][20][21][22] subpeptides.…”
Section: Introductionmentioning
confidence: 99%